Readiness to change physical activity and dietary practices and willingness to consult healthcare providers - Sweeney M Monica; Gousse Yolene; Cassells Andrea; Lees Emily; Hepworth Joseph T; Taylor Wendell C; Vaughn Anita; Tobin Jonathan N (BMC, 2004)
Abstract Background Complementary or discrepant stages of change for multiple risk behaviors can guide the development of effective risk reduction interventions for multiple risk factors. The objectives of this study were to assess readiness to change physical activity and dietary practices and the relationships among readiness scores for physical activity and dietary practices. In an underserved population, the readiness scores were analyzed in relationship to the patient's interest in communicating with healthcare providers about health behavior change. Healthcare providers are important contributors in promoting behavior change in community health centers. Methods Patients completed questionnaires about communicating with healthcare providers and readiness to change physical activity, intake of fruits and vegetables, dietary fat, calories and weight management. Frequency distributions, correlations, and analysis of variance were computed. Results Readiness to change physical activity was not related to readiness to change dietary practices. Readiness to change fruit and vegetable intake and readiness to change dietary fat intake were significantly related. Readiness to change and interest in communicating with healthcare providers were significantly related for physical activity but not for dietary practices. Conclusions Readiness to change behavior and interest in talking to healthcare providers were distinct dimensions; for physical activity, the dimensions were congruent and for dietary practices, the dimensions were unrelated. Readiness to change physical activity and dietary practices were not related (discrepant stages of readiness). Therefore, among underserved populations, sequential rather than simultaneous interventions may be appropriate when intervening on multiple risk behaviors, particularly physical activity and dietary practices.